Effectiveness of the biopesticide Amyloland and the two chemical pesticides in controlling of the red rusty flour beetle Tribolium castaneum (Herbst) - Ameen Taher Eesa; Mushtak Talib Mohammadali (Journal of Kerbala for Agricultural Sciences, 2024)
This study evaluated the efficiency of the bacterial biopesticide Amyloland and the two chemical pesticides Coragen and Conan in controlling adults and the second instar larvae of the red rusty flour beetle Tribolium castaneum under laboratory conditions. The results of the study showed that the pesticide Amyloland achieved the highest mortality percentage of second-instar larvae at a concentration of 3.5 g L-1, reaching 100% after 9 days of treatment, compared to the two concentrations of 2.5 and 3 g L-1, which recorded a mortality percentage of 73.33% and 96.67%, respectively, for the same time. In the treatment of adults, the concentration of 3.5 g L-1 gave the highest mortality percentage of 90% after 13 days of treatment compared to the two concentrations of 2.5 and 3 g L-1, which achieved a mortality percentage of 50% and 66.67%, respectively, for the same time. As for treating the two chemical pesticides, the Coragen pesticide achieved superiority and significant differences over the Conan pesticide in the adult instar. As for the treatment of the second larval instar, there are no significant differences between the two pesticides in the percentage of mortality during the treatment periods. The results of the Coragen pesticide indicated that the highest percentage of mortality for adults, at a concentration of 0.20 ml L-1, reached 100% after 9 days of treatment. The concentrations of 0.15 and 0.10 ml L-1 recorded a mortality percentage of 76.7% and 56.7%, respectively. As for Conan pesticide in the adult instar, it was given at a concentration of 0.6 g L-1, the highest mortality percentage of 63% after 9 days of treatment, while at the two concentrations of 0.5 and 0.4 g L-1, the percentage of mortality 50% and 43.3%, respectively. From the results, we notice that the percentage of mortality increases with increasing concentration and length of time.